Aerobic biotransformation of the antibiotic ciprofloxacin by Bradyrhizobium sp. isolated from activated sludge. (November 2018) - Nguyen, Luong N.; Nghiem, Long D.; Oh, Seungdae
Abstract: Ciprofloxacin (CIP) is an antibiotic that is widely used to treat bacterial infections and is poorly biodegraded during wastewater treatment. In this study, a CIP-degrading bacterial strain (GLC_01) was successfully retrieved from activated sludge by enrichment and isolation. The obtained bacterial strain shares over 99% nucleotide identity of the 16S rRNA gene with Bradyrhizobium spp. Results show that Bradyrhizobium sp. GLC_01 degraded CIP via cometabolism with another carbon substrate following a first-order kinetics degradation reaction. CIP degradation by Bradyrhizobium sp. GLC_01 increased when the concentration of the primary carbon source increased. The biodegradability of the primary carbon source also affected CIP degradation. The use of glucose and sodium acetate (i.e. readily biodegradable), respectively, as a primary carbon source enhanced CIP biotransformation, compared to starch (i.e. relatively slowly biodegradable). CIP degradation decreased with the increase of the initial CIP concentration. Over 70% CIP biotransformation was achieved at 0.05 mg L −1 whereas CIP degradation decreased to 26% at 10 mg L −1 . The phylogenetic identification and experimental verification of this CIP-degrading bacterium can lead to a bioengineering approach to manage antibiotics and possibly other persistent organic contaminants during wastewater treatment. Highlights: Bradyrhizobium sp. GLC_01 was isolated from activated sludge. GLC_01 removed CIP via cometabolism with primary carbon source. High concentration of the primary carbon source induced better removal of CIP. The primary carbon source degradability affected CIP removal. GLC_01 could remove 70% of CIP at environmentally relevant concentration.